2018
DOI: 10.1126/scitranslmed.aat0797
|View full text |Cite
|
Sign up to set email alerts
|

A dysbiotic microbiome triggers T H 17 cells to mediate oral mucosal immunopathology in mice and humans

Abstract: One Sentence Summary: Combined human and animal model studies conclusively implicate microbiota-triggered oral mucosal Th17 cells as drivers of local immunopathology and therapeutic targets in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
357
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(377 citation statements)
references
References 60 publications
18
357
1
1
Order By: Relevance
“…Notably, the advantage of GS‐9973 treatment is that it shows suppressive effect in bone loss even when administered after periodontitis induction, suggesting that the SYK inhibitor may be able to slow down progressive bone loss in human periodontitis. This is different from anti‐IL‐17A antibody administration in the same periodontitis model . The SYK inhibitor treatment may meet the requirements of clinical practice because intragingival injection, which would allow to reduce the dose and frequency of SYK inhibitor administration and lessen the risk for potential adverse events, could be considered as a route for administration in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the advantage of GS‐9973 treatment is that it shows suppressive effect in bone loss even when administered after periodontitis induction, suggesting that the SYK inhibitor may be able to slow down progressive bone loss in human periodontitis. This is different from anti‐IL‐17A antibody administration in the same periodontitis model . The SYK inhibitor treatment may meet the requirements of clinical practice because intragingival injection, which would allow to reduce the dose and frequency of SYK inhibitor administration and lessen the risk for potential adverse events, could be considered as a route for administration in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The SYK inhibitor treatment may meet the requirements of clinical practice because intragingival injection, which would allow to reduce the dose and frequency of SYK inhibitor administration and lessen the risk for potential adverse events, could be considered as a route for administration in humans. Recent investigations demonstrated that T H 17 cells that produce IL‐17A and IL‐17F are the primary drivers for the pathogenesis of periodontitis in mice and humans . These studies provided mechanistic and genetic justification that inhibition of IL‐17 family members or suppression of T H 17 cell development may be a plausible therapeutic option for treatment of alveolar bone resorption in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with mutations that disrupt interleukin‐17 signaling are prone to fungal infection . Interleukin‐17 receptor A null mice are more susceptible to oropharyngeal candidiasis caused by the commensal fungus Candida albicans than T helper 1‐deficient mice . However, exaggerated production of interleukin‐17 was also found in gingival tissues affected by periodontitis .…”
Section: Findings Of Transcriptome Studies In Gingivitis and Periodonmentioning
confidence: 99%
“…Periodontitis results from polymicrobial synergy and dysbiosis; however, periodontal tissue breakdown is mainly determined by the host's immune response, where the T‐lymphocyte subpopulations play a central role in the alveolar bone resorption that leads to tooth loss . In this context, T‐helper (Th)1 and Th17 lymphocytes have been related more to destructive events of periodontitis, while Th2 and T regulatory (Treg) lymphocytes have been related more to the suppression of the Th1 and Th17 responses, periodontitis remission, and periodontal healing …”
Section: Introductionmentioning
confidence: 99%